Two new species of Onciderini Thomson, 1860 (Coleoptera, Cerambycidae, Lamiinae) from South America - Nearns, Eugenio H.; Santos-Silva, Antonio (Zootaxa, 2016)
Two new species of Onciderini are described and illustrated: Oncideres tavakiliani, from Brazil (Pará), and Clavidesmus egeri, from Peru. Oncideres defectiofasciata Gilmour, 1950 is a junior synonym of O. chevrolatii Thomson, 1868. The following four new country records are reported: O. crassicornis Bates, 1865 (Paraguay); O. glebulenta Martins, 1981 (Paraguay); O. gutturator (Fabricius, 1775) (Venezuela); and O. repandator (Fabricius, 1793) (Peru).